The Role of Counseling Guidance in Early Childhood Education and Their Emotional Development - Kushendar Kushendar; Zara Mayra; Ika Ariyati (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2021)
Social development is the level of interaction of children with other people, ranging from parents, siblings, playmates, to society at large. While emotional development is an overflow of feelings when children interact with other people. Thus, socio-emotional development is a child's sensitivity to understand the feelings of others when interacting in everyday life.